#TITLE_ALTERNATIVE# - WIDIANTO , EKO
Since to find out the new field with proven play is more difficult and complicated, especially in North West Java basin and North East Java basin area, another approach had been applied. Mapping of structural and sedimentary basins of the Java Island has been carried out by using Bouguer gravity data. The objectives of those mapping are to discover and to find additional reserve, to increase production within existing basins and to study several rifted basins which are predicted still to have potential to generate hydrocarbon. In this study, examination and evaluation of the Bouguer gravity data consist of spectrum analysis, filtering, horizontal gradient determination, and deconvolution. The results show the presence of two discontinuity layers due to densities contrast at 2.35 km and 14 km respectively. Shallow discontinuity is predicted as an average depth of Tertiary basement and deep discontinuity is estimated as depth of Moho zone. The structural trend of rifted basin in West Java is aligned with Sumatra trend that is NW-SE, in Central Java is W-E. The trend of North East Java is NE-SW or parallel to Meratus trend, and in Central East Java is W-E. This study also reveals the existence of low-density contrast at 17.5 km depth that may relate to high temperature asthenospheric intrusive body in lithosphere. In several places, this asthenosphere intrusive body may reach lithosphere as shallow as 2.5 km depth and it is characterized by positive density contrast. Maturation study of the source rock interval (i.e. TAF and Ngimbang source rock) in the depocenter area confirms that the source rock is already in gas generation stage. On the contrary, in the shallower part of the basin the source rock interval is still in oil generation stage. This dissertation contributes to the geosciences such as an invention of the new method in gravity data evaluation that is very useful for mapping of sedimentary basin, especially rifted basin. The method combines moving average and second vertical derivative filtering with gravity data deconvolution. The result exhibits evolution of asthenosphere intrusion both vertically and horizontally, so that development stage of the basin can be recognized. In conclusion, twenty basins in Java may retain potential hydrocarbon as high as 41 BBOE (low estimate), 187 BBOE (high estimate) and 113 BBOE (best estimate).